2010
DOI: 10.1007/s11071-009-9648-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the synchronization manifold in nearest neighbor nonidentical van der Pol-like oscillators

Abstract: We investigate the stability of the synchronization manifold in a ring and in an open-ended chain of nearest neighbor coupled self-sustained systems, each self-sustained system consisting of multi-limit cycle van der Pol oscillators. Such a model represents, for instance, coherent oscillations in biological systems through the case of an enzymatic-substrate reaction with ferroelectric behavior in a brain waves model. The ring and open-ended chain of identical and nonidentical oscillators are considered separat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Using the decomposition u t ¼ UxðtÞ þ y; with xðtÞ 2 C p and y 2 Q 1 Q \ C 1 (C 1 is the subset of C consisting of continuously differentiable functions). Then we can decompose (17) as…”
Section: The Calculation Of Normal Forms On Center Manifolds and mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the decomposition u t ¼ UxðtÞ þ y; with xðtÞ 2 C p and y 2 Q 1 Q \ C 1 (C 1 is the subset of C consisting of continuously differentiable functions). Then we can decompose (17) as…”
Section: The Calculation Of Normal Forms On Center Manifolds and mentioning
confidence: 99%
“…In Ref. 17, the stability of the synchronization manifold in a ring and in an open-ended chain of nearest neighbor coupled self-sustained systems, each self-sustained system consisting of multilimit cycle van der Pol oscillators, has been investigated and it has been found that synchronization occurs in a system of many coupled modified van der Pol oscillators, and it is stable even in the presence of a spread of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these results have been validated experimentally and the consequences of parameter mismatch have been also emphasized [17]. But, these studies [16,17] and others [18][19][20] have considered only the influence of nearest neighbors coupling on stability boundaries using both analytical and numerical investigations. Thus, we want to investigate in this paper the modulatory effect of non-nearest neighbors and the local injection on synchronized states and their corresponding stability boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…[14]. The benefits of synchronization do not lie only in those situations where it can be found or explained in nature, but also in possible technological applications such as communication engineering, biology, chemistry and so on [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%